An Analysis of Fishermen's Economic Welfare: A Case Study of Catch-Based Financial Structures in the Talaud Islands Regency: Analisis Kesejahtraan Ekonomi Nelayan: Studi Kasus Struktrur Keuangan Berbasis Hasil Tangkapan di Kabupaten Kepulauan Talaud - Julita Inggrinne Nelwan; Cornelia Timpal; James Edward Lalira (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study examines the economic welfare of fishermen in Gemeh District, Talaud Islands Regency, with a focus on the financial structure based on fishing yields. The study aims to understand how financial support from fish buyers affects the income and overall economic well-being of fishermen. The financial assistance typically includes capital for fuel, basic family needs, and emergency expenses. A case study approach was used to gather in-depth data on the fishermen's economic conditions. The population consists of fishermen in Gemeh District, while the sample includes those who have adopted a catch-based financial system. Data collection involved interviews and Focus Group Discussions (FGD) with fishermen, government representatives, and community members. The data was analyzed using regression analysis to evaluate the relationship between fishing yields (independent variable) and fishermen’s income (dependent variable), alongside other factors like operational costs and financial aid. The regression analysis revealed a significant positive relationship between fishing yields and fishermen's income. Higher fishing yields were correlated with increased income, although high operational expenses often hindered optimal economic welfare. Fishermen who received capital from local fish buyers experienced moderate levels of economic welfare, while those who accessed financial institutions, such as banks, reported better financial stability. Furthermore, the fishermen's reliance on buyers for financial assistance sometimes resulted in increased debt and limited economic mobility. The findings suggest that while fishing yields directly impact fishermen’s income, their overall economic welfare is also influenced by operational expenses and the financial system in place. Fishermen with access to larger capital sources, such as banks, tend to have better financial outcomes than those reliant on local fish buyers. The results underscore the need for policies that reduce operational costs and improve access to fair financial resources, thereby enhancing fishermen's economic independence and well-being. This study concludes that improving the financial structure and providing more equitable access to capital will significantly impact the economic welfare of fishermen. Policies aimed at modernizing fishing tools, reducing operational costs, and offering broader financial options are critical to achieving sustainable economic welfare for fishermen in Gemeh District.